A green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity and a preparation method thereof
By using industrial waste such as desulfurization ash and other materials, an ultra-high performance concrete with ultra-high fracture toughness, high strength, high flowability and environmental protection characteristics was prepared, which solved the problems of insufficient ductility and strength of alkali-activated concrete in the prior art, and achieved the dual goals of high performance and environmental protection.
Patent Information
- Application Number
- CN202411243140.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-09-05
AI Technical Summary
How to use alkali-excited concrete to replace cement in ECC to prepare ultra-high performance concrete with ultra-high fracture toughness, high strength, high flowability and environmental protection characteristics.
The high-performance ultra-high-performance concrete is prepared by using desulfurization ash, coal gangue, red mud, hydrated gypsum, quartz sand, composite alkali triggers, water, dispersants, defoaming agents, modified sisal fibers and modified graphene-PE fibers through specific stirring and ultrasonic treatment methods.
Concrete with ultra-high fracture toughness, high strength, high flowability and environmental protection characteristics can be widely used in bridge and road projects, and at the same time solves the problem of industrial waste stacking, with good construction performance and durability.
Smart Images

Figure BDA0005029872220000171 
Figure BDA0005029872220000181
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ultra-high performance concrete, and in particular relates to a green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity and a preparation method thereof. Background Art
[0002] In the 1990s, Professor Victor C. Li of the University of Michigan systematically designed, adjusted and optimized the fiber, matrix and fiber-matrix interface system based on the principles of micro- and fracture mechanics, and proposed a design method for high-ductility fiber-reinforced cement-based composites, thereby developing ECC. ECC is a new type of cement-based composite material that can achieve smooth development of multiple microcracks and high ductility when the fiber content is moderate. It has good stress transfer and crack width control capabilities since the first crack is generated, and exhibits significant strain hardening and crack width controllability. Its ultimate strain can reach 3%-7%, while the ultimate tensile strain of ordinary concrete when cracking is only 0.01%-0.02%, and ECC is 200-500 times that. The ECC formula does not contain coarse aggregate, so this type of material uses a high amount of cement. The use of large amounts of cement not only increases costs, but is also not conducive to environmental protection.
[0003] In comparison, alkali-activated concrete is an amorphous three-dimensional network structure composed of silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons generated under alkali-activated conditions using industrial waste such as desulfurized ash and coal gangue. It is a green, environmentally friendly, low-cost cementitious material with excellent properties such as high temperature resistance, acid and alkali resistance, and solidification of heavy metals, but it also has disadvantages such as low ductility, low compressive strength, low tensile strength, and poor fluidity.
[0004] Therefore, how to use alkali-activated concrete to replace cement in ECC to prepare green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity has become a technical problem that technicians in this field need to solve urgently. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity and a preparation method thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The invention provides a green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity, comprising the following raw materials in parts by weight: 20-35 parts of desulfurized ash, 5-11 parts of coal gangue, 1-3 parts of red mud, 1-3 parts of gypsum, 33-40 parts of quartz sand, 10-19 parts of composite alkali activator, 5-9 parts of water, 0.02-0.04 parts of dispersant, 0.03-0.05 parts of defoamer, 1-3 parts of modified sisal fiber and 0.53-0.75 parts of modified graphene-PE fiber.
[0008] Preferably, the preparation method of the modified sisal fiber comprises the following steps: soaking the sisal fiber in a mixed solution of concentrated nitric acid and concentrated sulfuric acid for 3-4 hours, and rinsing to obtain the modified sisal fiber;
[0009] The volume ratio of the concentrated nitric acid to the concentrated sulfuric acid is (4-6):1;
[0010] The sisal fiber has a length of 25-30 mm, a diameter of 0.6-0.7 mm, and two ends of the sisal fiber have hooks.
[0011] Preferably, the preparation method of the modified graphene-PE fiber comprises the following steps: adding the modified graphene to N,N-dimethylformamide, ultrasonicating at 100-200W for 0.2-0.4h, then adding the modified polyethylene fiber, continuing ultrasonicating for 10h, washing and drying to obtain the modified graphene-PE fiber;
[0012] The mass ratio of the modified graphene to N,N-dimethylformamide is 1:2000;
[0013] The mass ratio of the modified graphene to the modified polyethylene fiber is (0.03-0.05):(0.5-0.7).
[0014] Preferably, the preparation method of the modified graphene comprises the following steps: placing the graphene in a mixed solution of concentrated nitric acid and concentrated sulfuric acid and stirring it fully, ultrasonically oscillating it at 20-30°C for 1-2h and then standing it, then diluting and centrifuging it, repeating the above dilution and centrifugation steps for the precipitate obtained by centrifugation until the pH value of the supernatant obtained by centrifugation is greater than 7, and then drying the obtained supernatant in a vacuum environment of 80-90°C and 40-50Pa to obtain the preliminary modified graphene; adding the obtained preliminary modified graphene to thionyl chloride, then adding a catalyst and ultrasonically oscillating it at 100-200W for 0.2-0.4h, and then refluxing it at 40-50°C for 6-10h to obtain the modified graphene;
[0015] The mass ratio of the graphene to the mixed solution of concentrated nitric acid and concentrated sulfuric acid is 1:(300-400), and the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 1:(5-6);
[0016] The mass ratio of the preliminarily modified graphene to thionyl chloride is 1:300;
[0017] The catalyst is N,N-dimethylformamide, and the mass ratio of the catalyst to the preliminarily modified graphene is (40-50):1.
[0018] Preferably, the preparation method of the modified polyethylene fiber comprises the following steps: cutting the polyethylene fiber into short fibers, and then soaking them in potassium hydroxide solution and sodium hydroxide solution in sequence to obtain preliminary modified polyethylene fibers; placing the preliminary modified polyethylene fibers in thionyl chloride solution and polyethyleneimine solution in sequence for ultrasonic treatment to obtain modified polyethylene fibers.
[0019] Preferably, the length of the short fibers is 6 mm;
[0020] The concentration of the potassium hydroxide solution is 2 mol / L, and the concentration of the sodium hydroxide solution is 2 mol / L;
[0021] The volume ratio of thionyl chloride to the solvent in the thionyl chloride solution is 1:(250-300), and the volume ratio of polyethyleneimine to the solvent in the polyethyleneimine solution is 1:(150-200).
[0022] Preferably, the content of SiO2 in the desulfurized ash is 50-60wt%, the content of Al2O3 is 15-20wt%, and the particle size is 2200-2800 mesh;
[0023] The content of Al2O3 in the red mud is 42-48wt%, and the content of SiO2 is 40-50wt%; the red mud is obtained by calcining kaolinite at 600-700°C for 6-9h, and then grinding and sieving to obtain calcined red mud with a particle size of less than 40nm;
[0024] The Ca2SO4 content in the plaster of Paris is greater than 97wt%, and the particle size is 4000-5000 mesh;
[0025] The average particle size of the coal gangue is 300-400nm;
[0026] The particle size of the quartz sand is 40-60 mesh;
[0027] The composite alkali activator is sodium water glass with a modulus of 2.0-2.6.
[0028] Preferably, the dispersant is sodium dodecyl sulfate; and the defoaming agent is tributyl phosphate.
[0029] The present invention also provides a method for preparing the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete described in the above technical solution, comprising the following steps:
[0030] (1) Weighing each raw material by weight, placing the dispersant, defoamer and water in the composite alkali activator, stirring for 180-240 seconds, and then ultrasonicating at 300-500W for 0.5-0.7h to obtain a mixed solution;
[0031] (2) Put desulfurized ash, red mud, plaster of Paris, coal gangue and quartz sand into a stirring pot and stir for 100-120 seconds to obtain a mixture;
[0032] (3) adding the mixed solution in step (1) to the mixed material in step (2) and stirring for 150-180 seconds, then adding the modified graphene-PE fiber, stirring slowly for 60-90 seconds, and then adding the modified sisal fiber, stirring rapidly for 90-120 seconds, and pouring, vibrating and curing to obtain the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete;
[0033] There is no order of precedence for steps (1) and (2).
[0034] Preferably, in step (1), the stirring speed is 60-90 r / min;
[0035] In step (2), the rotation speed of the dry stirring is 90-120 r / min;
[0036] In step (3), the stirring speed is 90-120 r / min, the slow stirring speed is 60-90 r / min, and the fast stirring speed is 120-150 r / min.
[0037] Compared with the prior art, the present invention has the following advantages and technical effects:
[0038] 1. The present invention uses alkali-activated concrete as a base material, and by adding modified sisal fiber and modified graphene-PE fiber, obtains ultra-high fracture toughness, high strength, high fluidity, green ultra-high performance concrete with the advantages of high fracture toughness and mechanical strength, fast setting speed, good fluidity, high construction performance and durability, which can be widely used in bridge engineering and road engineering.
[0039] 2. The ultra-high fracture toughness, high strength, and high fluidity green ultra-high performance concrete provided by the present invention uses desulfurization ash, coal gangue and other industrial wastes as raw materials, which can solve the problems of industrial waste stacking, turn waste into treasure, save resources, and protect the environment.
[0040] 3. The green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity provided by the present invention can be prepared at room temperature, has a fast setting time and a simple preparation method. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods.
[0043] The embodiment of the present invention provides a green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity, comprising the following raw materials in parts by weight: 20-35 parts of desulfurized ash, 5-11 parts of coal gangue, 1-3 parts of red mud, 1-3 parts of gypsum, 33-40 parts of quartz sand, 10-19 parts of composite alkali activator, 5-9 parts of water, 0.02-0.04 parts of dispersant, 0.03-0.05 parts of defoaming agent, 1-3 parts of modified sisal fiber and 0.53-0.75 parts of modified graphene-PE fiber.
[0044] The present invention uses alkali-activated concrete as a base material, and by internally adding modified sisal fiber and modified graphene-PE fiber, obtains ultra-high fracture toughness, high strength, high fluidity, green ultra-high performance concrete with the advantages of high fracture toughness and mechanical strength, fast setting speed, good fluidity, high construction performance and durability, and can be widely used in bridge engineering and road engineering.
[0045] In a preferred embodiment, the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete comprises 20-35 parts of desulfurized ash, preferably 25-28 parts, by weight.
[0046] In a preferred embodiment, the desulfurized ash contains 50-60wt% SiO2, 15-20wt% Al2O3 and has a particle size of 2200-2800 mesh.
[0047] In a preferred embodiment, the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete comprises 5-11 parts of coal gangue, preferably 7-9 parts, by weight.
[0048] In a preferred embodiment, the average particle size of the coal gangue is 300-400 nm.
[0049] In a preferred embodiment, the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete comprises 1-3 parts of red mud, preferably 2-3 parts, by weight.
[0050] In a preferred embodiment, the content of Al2O3 in the red mud is 42-48wt%, and the content of SiO2 is 40-50wt%; the red mud is calcined kaolinite at 600-700°C for 6-9h, and then ground and sieved to obtain calcined red mud with a particle size of less than 40nm.
[0051] In a preferred embodiment, the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete includes 1-3 parts of gypsum by weight.
[0052] In a preferred embodiment, the Ca2SO4 content in the plaster is greater than 97wt%, and the particle size is 4000-5000 mesh.
[0053] In a preferred embodiment, the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete comprises 33-40 parts by weight, preferably 36-38 parts by weight of quartz sand.
[0054] In a preferred embodiment, the particle size of the quartz sand is 40-60 mesh.
[0055] In a preferred embodiment, the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete comprises 10-19 parts of composite alkali activator, preferably 14-15 parts, by weight.
[0056] In a preferred embodiment, the composite alkali activator is sodium water glass with a modulus of 2.0-2.6; the preparation method of the composite alkali activator is: water glass with an initial modulus of 3.6-4.0 and a solid content of 30-34% and sodium hydroxide are configured to form sodium water glass with a modulus of 2.0-2.6, and then aged for 6-10 hours to obtain the composite alkali activator. The present invention makes the formed green ultra-high performance concrete more stable by adding sodium water glass with a modulus of 2.0-2.6 as a composite alkali activator.
[0057] In a preferred embodiment, the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete comprises 5-9 parts of water, preferably 7-8 parts, by weight.
[0058] In a preferred embodiment, the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete includes 0.02-0.04 parts of dispersant by weight; the dispersant is sodium dodecyl sulfate.
[0059] In a preferred embodiment, the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete includes 0.03-0.05 parts of defoaming agent by weight; the defoaming agent is tributyl phosphate.
[0060] In a preferred embodiment, the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete includes 1-3 parts of modified sisal fiber, preferably 1-2 parts by weight. The modified sisal fiber in the present invention has the advantage of a large elastic modulus, and mainly plays a role in improving the toughness and strength of concrete. If the amount added is too large, agglomeration will form in the matrix, resulting in a decrease in the mechanical strength of the matrix.
[0061] In a preferred embodiment, the preparation method of the modified sisal fiber comprises the following steps: soaking the sisal fiber in a mixed solution of concentrated nitric acid and concentrated sulfuric acid for 3-4 hours, and rinsing to obtain the modified sisal fiber. The present invention uses a mixed solution of concentrated nitric acid and concentrated sulfuric acid to treat the sisal fiber, removes wood residues and other substances on the surface of the sisal fiber, increases the interface bonding strength between the sisal fiber and the matrix, and further enhances the mechanical strength and toughness of the matrix.
[0062] In a preferred embodiment, the volume ratio of concentrated nitric acid to concentrated sulfuric acid is (4-6):1.
[0063] In a preferred embodiment, the sisal fiber has a length of 25-30 mm, a diameter of 0.6-0.7 mm, and hooks at both ends.
[0064] In a preferred embodiment, the reagent used for flushing is anhydrous ethanol.
[0065] In a preferred embodiment, the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete includes 0.53-0.75 parts of modified graphene-PE fiber, preferably 0.6-0.71 parts by weight. The modified graphene in the modified graphene-PE fiber mainly plays the effects of nano-nucleation, nano-filling, nano-bridging, etc., optimizes the pore structure of the matrix, reduces the porosity, enhances the density, and improves the mechanical strength; the modified PE fiber mainly plays a role in greatly improving the toughness and strength of the matrix. The modified graphene in the present invention is nano-level, the modified PE fiber is micron-level, and the sisal fiber is millimeter-level, which improves the toughness and strength of the matrix from different scales.
[0066] In a preferred embodiment, the preparation method of the modified graphene-PE fiber comprises the following steps: adding the modified graphene to N,N-dimethylformamide, ultrasonicating at 100-200W for 0.2-0.4h, then adding the modified polyethylene fiber, continuing ultrasonicating for 10h, washing and drying to obtain the modified graphene-PE fiber. The present invention prepares the modified graphene-PE fiber by mixing and ultrasonicating the modified graphene and the modified polyethylene fiber, thereby grafting the modified graphene on the PE fiber, thereby avoiding the defect of decreased mechanical strength of the matrix caused by the use of traditional dispersants when the modified graphene and modified polypropylene fiber are separately incorporated.
[0067] In a preferred embodiment, the mass ratio of the modified graphene to N,N-dimethylformamide is 1:2000.
[0068] In a preferred embodiment, the mass ratio of the modified graphene to the modified polyethylene fiber is (0.03-0.05):(0.5-0.7). The present invention controls the mass ratio of the modified graphene to the modified polyethylene fiber within the above range, which has the advantage of significantly improving the toughness and strength of the matrix. Too much modified graphene will cause the matrix to form "agglomeration" phenomenon, which in turn causes defects in the matrix; too little modified graphene will not achieve a specific effect.
[0069] In a preferred embodiment, the washing reagent is ethanol; the drying temperature is 70-80° C., and the drying method is vacuum drying.
[0070] In a preferred embodiment, the preparation method of the modified graphene comprises the following steps: placing the graphene in a mixed solution of concentrated nitric acid and concentrated sulfuric acid and stirring it thoroughly, ultrasonically oscillating it at 20-30°C for 1-2 hours and then standing it, then diluting and centrifuging it, repeating the above dilution and centrifugation steps for the precipitate obtained by centrifugation until the pH value of the supernatant obtained by centrifugation is greater than 7, and then drying the obtained supernatant in a vacuum environment of 80-90°C and 40-50Pa to obtain preliminary modified graphene; adding the obtained preliminary modified graphene to thionyl chloride, and then adding a catalyst to ultrasonicate at 100-200W for 0.2-0.4h, and then refluxing at 40-50°C for 6-10h to obtain the modified graphene.
[0071] In a preferred embodiment, the mass ratio of the graphene to the mixed solution of concentrated nitric acid and concentrated sulfuric acid is 1:(300-400), and the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 1:(5-6). The present invention uses a mixed solution of concentrated nitric acid and concentrated sulfuric acid to treat graphene, thereby obtaining a preliminary modified graphene with a large number of hydroxyl groups and carboxyl groups on the surface. Too much or too little use of the mixed solution will affect the number of hydroxyl groups or carboxyl groups grafted on the surface.
[0072] In a preferred embodiment, the standing time is 1.5 hours; and the diluent for dilution is deionized water.
[0073] In a preferred embodiment, the mass ratio of the preliminarily modified graphene to thionyl chloride is 1:300; the catalyst is N,N-dimethylformamide, and the mass ratio of the catalyst to the preliminarily modified graphene is (40-50): 1. The present invention uses thionyl chloride to modify graphene to obtain graphene containing chlorine groups on the surface, thereby improving the dispersion performance of graphene, and utilizing the nano-nucleation, nano-filling, nano-bridging and other system effects of graphene to improve the mechanical strength of concrete.
[0074] In a preferred embodiment, the method for preparing the modified polyethylene fiber comprises the following steps: cutting the polyethylene fiber into short fibers, and then soaking them in potassium hydroxide solution and sodium hydroxide solution in sequence to obtain preliminary modified polyethylene fibers; placing the preliminary modified polyethylene fibers in thionyl chloride solution and polyethyleneimine solution in sequence for ultrasonic treatment to obtain modified polyethylene fibers.
[0075] In a preferred embodiment, the diameter of the polyethylene fiber is 30-60 μm.
[0076] In a preferred embodiment, the length of the short fibers is 6 mm. In the present invention, the polyethylene fibers are cut into short fibers, which can play a bridging role in concrete.
[0077] In a preferred embodiment, the polyethylene fibers are cut into short fibers and then further cleaned and dried; the cleaning is performed by reflux cleaning with an acetone solution at 80° C.; and the drying is performed by vacuum drying.
[0078] In a preferred embodiment, the concentration of the potassium hydroxide solution is 2 mol / L, and the concentration of the sodium hydroxide solution is 2 mol / L. The potassium hydroxide solution in the present invention can preliminarily remove impurities on the surface of the polyethylene fiber, and the sodium hydroxide solution can further remove impurities on the surface of the polyethylene fiber.
[0079] In a preferred embodiment, the soaking time of the potassium hydroxide solution is 0.6-0.8h; the soaking time of the sodium hydroxide solution is 10min.
[0080] In a preferred embodiment, the volume ratio of thionyl chloride to solvent in the thionyl chloride solution is 1:(250-300), and the solvent of the thionyl chloride solution is N,N-dimethylformamide; the volume ratio of polyethyleneimine to solvent in the polyethyleneimine solution is 1:(150-200), and the solvent of the polyethyleneimine solution is N-methylpyrrolidone. The thionyl chloride solution in the present invention can graft chlorine groups on the surface of polyethylene fibers, and the polyethyleneimine solution can graft amino groups on the surface of polyethylene fibers.
[0081] In a preferred embodiment, the power of ultrasonic treatment of the initially modified polyethylene fiber in thionyl chloride solution is 100-200 W, and the time is 0.2-0.4 h; the power of ultrasonic treatment of the initially modified polyethylene fiber in polyethyleneimine solution is 100-200 W, and the time is 0.2-0.4 h.
[0082] The present invention also provides a method for preparing the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete described in the above technical solution, comprising the following steps:
[0083] (1) Weighing each raw material by weight, placing the dispersant, defoamer and water in the composite alkali activator, stirring for 180-240 seconds, and then ultrasonicating at 300-500W for 0.5-0.7h to obtain a mixed solution;
[0084] (2) Put desulfurized ash, red mud, plaster of Paris, coal gangue and quartz sand into a stirring pot and stir for 100-120 seconds to obtain a mixture;
[0085] (3) adding the mixed solution in step (1) to the mixed material in step (2) and stirring for 150-180 seconds, then adding the modified graphene-PE fiber, stirring slowly for 60-90 seconds, and then adding the modified sisal fiber, stirring rapidly for 90-120 seconds, and pouring, vibrating and curing to obtain the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete;
[0086] There is no order of precedence for steps (1) and (2).
[0087] The present invention ensures uniform dispersion of the modified graphene-PE fiber in concrete by first adding the modified graphene-PE fiber and stirring slowly, and then adds the modified sisal fiber and stirs quickly to ensure full dispersion of the modified sisal fiber in concrete, thereby giving full play to the role of each component in concrete.
[0088] In a preferred embodiment, in step (1), the stirring speed is 60-90 r / min;
[0089] In step (2), the rotation speed of the dry stirring is 90-120 r / min;
[0090] In step (3), the stirring speed is 90-120 r / min, the slow stirring speed is 60-90 r / min, and the fast stirring speed is 120-150 r / min.
[0091] Unless otherwise specified, parts in the embodiments of the present invention represent “parts by weight”.
[0092] In the following examples, the standard curing conditions are: curing for 28 days at a temperature of 20±2°C and a relative humidity of 95%RH or more;
[0093] The content of SiO2 in the desulfurized ash is 55wt%, the content of Al2O3 is 18wt%, and the particle size is 2500 mesh;
[0094] The content of Al2O3 in the red mud is 46wt%, the content of SiO2 is 45wt%, and the red mud is obtained by calcining kaolinite at 650℃ for 7h, then grinding and sieving to obtain calcined red mud with a particle size of less than 40nm;
[0095] The content of Ca2SO4 in the plaster of Paris is 98wt% and the particle size is 4500 mesh;
[0096] The average particle size of coal gangue is 350nm;
[0097] The particle size of quartz sand is 45 mesh;
[0098] The composite alkali activator is sodium water glass with a modulus of 2.3;
[0099] The dispersant is sodium dodecyl sulfate;
[0100] The defoaming agent is tributyl phosphate;
[0101] The concentration of concentrated sulfuric acid is 97wt%;
[0102] The concentration of concentrated nitric acid is 98wt%;
[0103] The diameter of polyethylene fibers is 30-60 μm.
[0104] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0105] Example 1
[0106] A method for preparing green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity, the specific steps are as follows:
[0107] (1) 28 parts of desulfurized ash, 8 parts of coal gangue, 2 parts of red mud, 2 parts of gypsum and 37 parts of quartz sand were poured into a mixer and stirred at 60 r / min for 100 s to obtain a mixture;
[0108] (2) 0.03 parts of dispersant, 0.04 parts of defoamer and 7 parts of water were placed in 15 parts of composite alkali excitation solution, stirred at 90 r / min for 180 s, and then ultrasonicated at 300 W for 0.5 h to obtain a mixed solution;
[0109] (3) adding the mixed solution in step (2) to the mixture in step (1), stirring at 90 r / min for 150 s, then adding 0.53 parts of modified graphene-PE fiber, stirring at 60 r / min for 60 s, then adding 1 part of modified sisal fiber, stirring at 120 r / min for 90 s, then pouring, vibrating, and curing for 28 days under standard curing conditions to obtain ultra-high fracture toughness, high strength, and high fluidity green ultra-high performance concrete;
[0110] The preparation method of the modified graphene-PE fiber is as follows: adding the modified graphene to N,N-dimethylformamide (the mass ratio of the modified graphene to the N,N-dimethylformamide is 1:2000), ultrasonicating for 0.3 h at a power of 150 W, then adding the modified polyethylene fiber (the mass ratio of the modified graphene to the modified polyethylene fiber is 0.03:0.5), continuing ultrasonicating for 10 h, then washing with ethanol, and vacuum drying at 75 ° C to obtain the modified graphene-PE fiber;
[0111] The preparation method of modified graphene is as follows: placing graphene in a mixed solution of concentrated nitric acid and concentrated sulfuric acid, wherein the mass ratio of graphene to the mixed solution is 1:350, and the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 1:5.5, then stirring fully, ultrasonically oscillating at 25°C for 1h and then standing for 1.5h, then diluting with deionized water, centrifuging, repeating the above dilution and centrifugation steps for the obtained precipitate until the pH value of the obtained supernatant is greater than 7, then drying the obtained supernatant in a vacuum environment of 85°C and 45Pa to obtain preliminary modified graphene; adding the preliminary modified graphene to thionyl chloride (the mass ratio of the preliminary modified graphene to thionyl chloride is 1:300), then dropping N,N-dimethylformamide as a catalyst (the mass ratio of N,N-dimethylformamide to the preliminary modified graphene is 45:1), then ultrasonicating at a power of 150W for 0.3h, and then refluxing at 45°C for 8h to obtain modified graphene;
[0112] The preparation method of the modified polyethylene fiber is as follows: the polyethylene fiber is cut into short fibers with a length of 6 mm, then reflux-cleaned with acetone at 80°C, vacuum-dried, then immersed in a 2 mol / L potassium hydroxide solution for 0.7 h, washed with ethanol, vacuum-dried, then immersed in a 2 mol / L sodium hydroxide solution for 10 min, then washed with ethanol, and vacuum-dried at 80°C to obtain a preliminary modified polyethylene fiber; the preliminary modified polyethylene fiber is placed in a thionyl chloride solution (the thionyl chloride solution is prepared by mixing thionyl chloride and N,N-dimethylformamide in a volume ratio of 1:280) and ultrasonically treated at a power of 150 W for 0.3 h, washed with ethanol, vacuum-dried at 80°C, and then placed in a polyethyleneimine solution (the polyethyleneimine solution is prepared by mixing polyethyleneimine and N-methylpyrrolidone in a volume ratio of 1:180) and ultrasonically treated at a power of 150 W for 0.3 h, washed with ethanol, and vacuum-dried at 30°C to obtain a modified polyethylene fiber;
[0113] The preparation method of modified sisal fiber is as follows: immerse the sisal fiber in a mixed solution of concentrated nitric acid and concentrated sulfuric acid for 3.5 hours, wherein the volume ratio of concentrated nitric acid to concentrated sulfuric acid in the mixed solution is 5:1, and then rinse with a large amount of anhydrous ethanol to obtain the modified sisal fiber; the sisal fiber has a length of 25-30 mm, a diameter of 0.6-0.7 mm, and has hooks at both ends.
[0114] Example 2
[0115] A method for preparing green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity, the specific steps are as follows:
[0116] (1) 27 parts of desulfurized ash, 9 parts of coal gangue, 3 parts of red mud, 1 part of gypsum and 38 parts of quartz sand were poured into a mixer and stirred at 90 r / min for 100 s to obtain a mixture;
[0117] (2) 0.03 parts of dispersant, 0.04 parts of defoamer and 7 parts of water were placed in 15 parts of composite alkali excitation solution, stirred at 120 r / min for 210 s, and then ultrasonicated at 400 W for 0.6 h to obtain a mixed solution;
[0118] (3) adding the mixed solution in step (2) to the mixture in step (1), stirring at 120 r / min for 165 s, then adding 0.75 parts of modified graphene-PE, stirring at 90 r / min for 75 s, then adding 1 part of modified sisal fiber, stirring at 150 r / min for 105 s, then pouring, vibrating, and curing for 28 days under standard curing conditions to obtain ultra-high fracture toughness, high strength, and high fluidity green ultra-high performance concrete;
[0119] The preparation methods of modified graphene-PE fiber, modified graphene, modified polyethylene fiber and modified sisal fiber are the same as those in Example 1.
[0120] Example 3
[0121] A method for preparing green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity, the specific steps are as follows:
[0122] (1) 25 parts of desulfurized ash, 9 parts of coal gangue, 3 parts of red mud, 3 parts of gypsum and 37 parts of quartz sand were poured into a mixer and stirred at 75 r / min for 100 s to obtain a mixture;
[0123] (2) 0.04 parts of dispersant, 0.02 parts of defoamer and 7 parts of water were placed in 15 parts of composite alkali excitation solution, stirred at 100 r / min for 240 s, and then ultrasonicated at 500 W for 0.7 h to obtain a mixed solution;
[0124] (3) adding the mixed solution in step (2) to the mixture in step (1), stirring at 90 r / min for 180 s, then adding 0.60 parts of modified graphene-PE fiber, stirring at 90 r / min for 90 s, then adding 1 part of modified sisal fiber, stirring at 120 r / min for 120 s, then pouring, vibrating, and curing for 28 days under standard curing conditions to obtain ultra-high fracture toughness, high strength, and high fluidity green ultra-high performance concrete;
[0125] The preparation methods of modified graphene-PE fiber, modified graphene, modified polyethylene fiber and modified sisal fiber are the same as those in Example 1.
[0126] Example 4
[0127] A method for preparing green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity, the specific steps are as follows:
[0128] (1) 28 parts of desulfurized ash, 8 parts of coal gangue, 2 parts of red mud, 2 parts of gypsum and 37 parts of quartz sand were poured into a mixer and stirred at 90 r / min for 100 s to obtain a mixture;
[0129] (2) 0.03 parts of dispersant, 0.04 parts of defoamer and 8 parts of water were placed in 14 parts of composite alkali excitation solution, stirred at 100 r / min for 180 s, and then ultrasonicated at 300 W for 0.5 h to obtain a mixed solution;
[0130] (3) adding the mixed solution in step (2) to the mixture in step (1), stirring at 90 r / min for 180 s, then adding 0.71 parts of modified graphene-PE fiber, stirring at 75 r / min for 90 s, then adding 1 part of modified sisal fiber, stirring at 120 r / min for 120 s, then pouring, vibrating, and curing for 28 days under standard curing conditions to obtain ultra-high fracture toughness, high strength, and high fluidity green ultra-high performance concrete;
[0131] The preparation methods of modified graphene-PE fiber, modified graphene, modified polyethylene fiber and modified sisal fiber are the same as those in Example 1.
[0132] Example 5
[0133] A method for preparing green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity, the specific steps are as follows:
[0134] (1) 27 parts of desulfurized ash, 9 parts of coal gangue, 2 parts of red mud, 2 parts of gypsum and 37 parts of quartz sand were poured into a mixer and stirred at 60 r / min for 100 s to obtain a mixture;
[0135] (2) 0.03 parts of dispersant, 0.04 parts of defoamer and 8 parts of water were placed in 14 parts of composite alkali excitation solution, stirred at 90 r / min for 240 s, and then ultrasonicated at 500 W for 0.7 h to obtain a mixed solution;
[0136] (3) adding the mixed solution in step (2) to the mixture in step (1), stirring at 120 r / min for 150 s, then adding 0.65 parts of modified graphene-PE fiber, stirring at 60 r / min for 60 s, then adding 1 part of modified sisal fiber, stirring at 120 r / min for 90 s, then pouring, vibrating, and curing for 28 days under standard curing conditions to obtain ultra-high fracture toughness, high strength, and high fluidity green ultra-high performance concrete;
[0137] The preparation methods of modified graphene-PE fiber, modified graphene, modified polyethylene fiber and modified sisal fiber are the same as those in Example 1.
[0138] Example 6
[0139] A method for preparing green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity, the specific steps are as follows:
[0140] (1) 26 parts of desulfurized ash, 8 parts of coal gangue, 3 parts of red mud, 3 parts of gypsum and 37 parts of quartz sand were poured into a mixer and stirred at 60 r / min for 100 s to obtain a mixture;
[0141] (2) 0.03 parts of dispersant, 0.04 parts of defoamer and 8 parts of water were placed in 14 parts of composite alkali excitation solution, stirred at 100 r / min for 180 s, and then ultrasonicated at 400 W for 0.6 h to obtain a mixed solution;
[0142] (3) adding the mixed solution in step (2) to the mixture in step (1), stirring at 90 r / min for 170 s, then adding 0.69 parts of modified graphene-PE fiber, stirring at 75 r / min for 75 s, then adding 1 part of modified sisal fiber, stirring at 150 r / min for 100 s, then pouring, vibrating, and curing for 28 days under standard curing conditions to obtain ultra-high fracture toughness, high strength, and high fluidity green ultra-high performance concrete;
[0143] The preparation methods of modified graphene-PE fiber, modified graphene, modified polyethylene fiber and modified sisal fiber are the same as those in Example 1.
[0144] Comparative Example 1
[0145] The difference from Example 1 is that the modified sisal fiber is omitted, and the rest is the same as Example 1.
[0146] Comparative Example 2
[0147] The difference from Example 1 is that the modified graphene-PE fiber is omitted, and the rest is the same as Example 1.
[0148] Comparative Example 3
[0149] The difference from Example 1 is that the modified sisal fiber and the modified graphene-PE fiber are omitted, and the rest is the same as Example 1.
[0150] Comparative Example 4
[0151] The difference from Example 1 is that in step (3), the mixed solution in step (2) is added to the mixture in step (1), stirred at 90 r / min for 170 s, then 0.03 parts of modified graphene and 0.5 parts of modified polyethylene fiber are added, stirred at 60 r / min for 75 s, then 1 part of modified sisal fiber is added, stirred at 120 r / min for 100 s, then poured, vibrated, and cured under standard curing conditions for 28 days to obtain green ultra-high performance concrete, and the rest is the same as Example 1;
[0152] The preparation methods of modified graphene, modified polyethylene fiber and modified sisal fiber are the same as those in Example 1.
[0153] The performance of the ultra-high performance concrete prepared in Examples 1-6 and Comparative Examples 1-4 was tested in accordance with GB / T 228-2002 “Methods for tensile testing of metallic materials” and JC / T 951-2005 “Test methods for crack resistance of cement mortar”. The test results are shown in Table 1.
[0154] Table 1 Performance of ultra-high performance concrete prepared in Examples 1-6 and Comparative Examples 1-4
[0155]
[0156]
[0157] As can be seen from Table 1, modified sisal fiber and modified graphene-PE fiber are added into Examples 1-6, which improves the strength, toughness, fluidity and durability of the matrix from the nanometer, micrometer and millimeter scales.
[0158] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A green ultra-high performance concrete with ultra-high fracture toughness, high strength and high fluidity, characterized in that: The invention comprises the following raw materials in parts by weight: 20-35 parts of desulfurized ash, 5-11 parts of coal gangue, 1-3 parts of red mud, 1-3 parts of gypsum, 33-40 parts of quartz sand, 10-19 parts of composite alkali activator, 5-9 parts of water, 0.02-0.04 parts of dispersant, 0.03-0.05 parts of defoaming agent, 1-3 parts of modified sisal fiber and 0.53-0.75 parts of modified graphene-PE fiber; The preparation method of the modified sisal fiber comprises the following steps: soaking the sisal fiber in a mixed solution of concentrated nitric acid and concentrated sulfuric acid for 3-4 hours, and rinsing to obtain the modified sisal fiber; the volume ratio of the concentrated nitric acid to the concentrated sulfuric acid is (4-6):1; the sisal fiber has a length of 25-30 mm, a diameter of 0.6-0.7 mm, and hooks at both ends; The preparation method of the modified graphene-PE fiber comprises the following steps: adding the modified graphene to N,N-dimethylformamide, ultrasonicating at 100-200W for 0.2-0.4h, then adding the modified polyethylene fiber, continuing ultrasonicating for 10h, washing and drying to obtain the modified graphene-PE fiber; the mass ratio of the modified graphene to the N,N-dimethylformamide is 1:2000; the mass ratio of the modified graphene to the modified polyethylene fiber is (0.03-0.05):(0.5-0.7); The preparation method of modified graphene comprises the following steps: placing graphene in a mixed solution of concentrated nitric acid and concentrated sulfuric acid and stirring the graphene fully, ultrasonically shaking at 20-30°C for 1-2h, then standing, diluting and centrifuging, repeating the above dilution and centrifugation steps for the precipitate obtained by centrifugation until the pH value of the supernatant obtained by centrifugation is greater than 7, and then drying the supernatant obtained in a vacuum environment at 80-90°C and 40-50Pa to obtain preliminary modified graphene; adding the preliminary modified graphene obtained to thionyl chloride, and then adding a catalyst; The agent is ultrasonicated at 100-200W for 0.2-0.4h, and then refluxed at 40-50°C for 6-10h to obtain the modified graphene; the mass ratio of the graphene to the mixed solution of concentrated nitric acid and concentrated sulfuric acid is 1:(300-400), and the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 1:(5-6); the mass ratio of the preliminary modified graphene to thionyl chloride is 1:300; the catalyst is N,N-dimethylformamide, and the mass ratio of the catalyst to the preliminary modified graphene is (40-50):1; The preparation method of the modified polyethylene fiber comprises the following steps: cutting the polyethylene fiber into short fibers, and then soaking them in potassium hydroxide solution and sodium hydroxide solution in sequence to obtain the initially modified polyethylene fiber; and placing the initially modified polyethylene fiber in thionyl chloride solution and polyethyleneimine solution in sequence to perform ultrasonic treatment to obtain the modified polyethylene fiber.
2. The ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete according to claim 1, characterized in that: In the preparation method of modified polyethylene fiber, the length of the short fiber is 6 mm; The concentration of the potassium hydroxide solution is 2 mol / L, and the concentration of the sodium hydroxide solution is 2 mol / L; The volume ratio of thionyl chloride to the solvent in the thionyl chloride solution is 1:(250-300), and the volume ratio of polyethyleneimine to the solvent in the polyethyleneimine solution is 1:(150-200).
3. The ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete according to claim 1, characterized in that: The desulfurized ash has a SiO2 content of 50-60wt%, an Al2O3 content of 15-20wt%, and a particle size of 2200-2800 mesh; The content of Al2O3 in the red mud is 42-48wt%, and the content of SiO2 is 40-50wt%; the red mud is obtained by calcining kaolinite at 600-700°C for 6-9h, and then grinding and sieving to obtain calcined red mud with a particle size of less than 40nm; The CaSO4 content in the plaster of Paris is greater than 97wt%, and the particle size is 4000-5000 mesh; The average particle size of the coal gangue is 300-400nm; The particle size of the quartz sand is 40-60 mesh; The composite alkali activator is sodium water glass with a modulus of 2.0-2.
6.
4. The ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete according to claim 1, characterized in that: The dispersant is sodium dodecyl sulfate; the defoaming agent is tributyl phosphate.
5. The method for preparing the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Weighing each raw material by weight, placing the dispersant, defoamer and water in the composite alkali activator, stirring for 180-240 seconds, and then ultrasonicating at 300-500W for 0.5-0.7h to obtain a mixed solution; (2) Put desulfurized ash, red mud, plaster of Paris, coal gangue and quartz sand into a stirring pot and dry-mix for 100-120 seconds to obtain a mixture; (3) adding the mixed solution in step (1) to the mixed material in step (2) and stirring for 150-180 seconds, then adding the modified graphene-PE fiber, stirring slowly for 60-90 seconds, and then adding the modified sisal fiber, stirring rapidly for 90-120 seconds, and pouring, vibrating and curing to obtain the ultra-high fracture toughness, high strength, high fluidity green ultra-high performance concrete; There is no order of precedence for steps (1) and (2).
6. The preparation method according to claim 5, characterized in that: In step (1), the stirring speed is 60-90 r / min; In step (2), the rotation speed of the dry stirring is 90-120 r / min; In step (3), the stirring speed is 90-120 r / min, the slow stirring speed is 60-90 r / min, and the fast stirring speed is 120-150 r / min.
Citation Information
Patent Citations
Concrete modified by graphene / fiber composite material and preparation method thereof
CN109231914A
Method for preparing graphene-plant fiber compound
CN109721269A